Clustering analysis of risk factors for non-suicidal self-injury behaviors in adolescents: a cross-sectional study of western China - Hou, Xin; Wu, Yuhang; Zhao, Jiayu; Luo, Jing; He, Jinglong; Kang, Qian; Li, Xuehua; Yu, Ling; Tang, Lei; Yong, Na; Luo, Jiaming (Frontiers in Psychiatry, 2025)
Background and objectivesThe analysis of clustering characteristics of disease risk factors makes for the formulation of corresponding prevention and control policies, but the risk factors for non-suicidal self-injury (NSSI) behaviors in adolescents is not covered, so this study is intended to explore the clustering characteristics of risk factors for NSSI behaviors in adolescents in the multi-center primary and secondary schools in western China.MethodsUtilizing random cluster sampling method, a total of 13,784 primary and secondary school students who met the research standards were randomly selected as the survey subjects from January 2020 to January 2021, and the clustering situation of the seven risk factors (depression, anxiety, stress, low social support, tolerance, avoidance, and emotional venting) among the students was analyzed. The characteristics of the respondents with a high clustering degree of risk factors for NSSI behaviors were also identified with the hierarchical logistic regression analysis.Results4.2% of the adolescents in western China were detected with NSSI behaviors in the past year; the risk factors were grouped into 4 clusters, ranging from level 0 to level 3, with each level including 7692 (55.8%), 3847 (27.9%), 1303 (9.5%) and 941 (6.8%) of the survey subjects, respectively. The results of the Cochran-Armitage trend test analysis showed that there existed a linear trend between the clustering degree of risk factors and the detection rate of NSSI behaviors (P<0.000); according to the hierarchical Logistic regression analysis, the clustering degree of risk factors for NSSI behaviors was higher in the adolescents whose parents divorced and remarried 1.21(0.016~0.373) and whose fathers received only primary school education or below 1.23 (0.005~0.404). By contrast, the degree was lower in the adolescents who are male 0.93(-0.132~-0.003) and had never attended boarding school 0.83(-0.286~-0.096), whose parents were not divorced 0.80 ( -0.367~-0.072 ), and whose fathers were farmers 0.87(-0.271~0.006).ConclusionThe risk factors for NSSI behaviors in adolescents are in clusters. As the risk factors continue to cluster, NSSI behaviors can be detected more easily in adolescents. With respect to the endeavors to prevent and control NSSI behaviors in adolescents, more attention should be focused on the mental health of the adolescents who are female and attend boarding schools, whose parents have broken marriages, and whose fathers have low literacy.